2022
DOI: 10.1515/shll-2022-2055
|View full text |Cite
|
Sign up to set email alerts
|

Creaky Voice and Prosodic Boundaries in Spanish: An Acoustic Study

Abstract: This study investigates vocalic creak in connection to the demarcation of prosodic boundaries in Spanish. Data from a picture task from 10 native Spanish speakers from diverse dialects was examined word-medially and word-finally. A total of 800 vowels were analyzed acoustically to determine if they involved creak; duration of creak relative to vowel duration was also recorded. The role of prosodic context, vowel quality and gender were examined. Our results show that creak is one of the cues that signals the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Specifically, creaky voice was coded when one or more of the following acoustic cues was present: aperiodicity (non-regular duration of pulses), creak (gradual pulse widening with F0 lowering and damping), diplophonia (variable pulse amplitude or shape), glottal squeak (sudden F0 increase), or the presence of a glottal stop. González et al (2022) found a prevalence of creaky voice word-finally for vowels across several Spanish dialects, particularly for men, and at the end of higher prosodic constituents. The data were originally examined for creaky voice only, but further inspection showed that at least some of the vowels coded as creaky tended to end in a noisy and/or non-periodic interval which could be consistent with breathy voice and/or devoicing.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Specifically, creaky voice was coded when one or more of the following acoustic cues was present: aperiodicity (non-regular duration of pulses), creak (gradual pulse widening with F0 lowering and damping), diplophonia (variable pulse amplitude or shape), glottal squeak (sudden F0 increase), or the presence of a glottal stop. González et al (2022) found a prevalence of creaky voice word-finally for vowels across several Spanish dialects, particularly for men, and at the end of higher prosodic constituents. The data were originally examined for creaky voice only, but further inspection showed that at least some of the vowels coded as creaky tended to end in a noisy and/or non-periodic interval which could be consistent with breathy voice and/or devoicing.…”
Section: Introductionmentioning
confidence: 88%
“…In a previous study, González et al (2022) examined the occurrence of creaky voice in word-final Spanish vowels. Creaky voice was analyzed via visual inspection of waveforms and spectrograms, following Dilley et al (1996), Redi and Shattuck-Hufnagel (2001) and Ladefoged and Maddieson (1996).…”
Section: Introductionmentioning
confidence: 99%
“…Creak, though commonly discussed in English, is also increasingly found in Spanish. For example, González et al (2022) analyzed the occurrence of creaky voice in 10 speakers from a variety of Spanish-speaking countries (Argentina, Bolivia, Colombia, Cuba, Peru, Puerto Rico, Spain, and Venezuela), and found that creaky voice was pervasive in word-final position. They also found that creak was more common among men than women, and with low vowels.…”
Section: Phrase-final Breath and Phrase-final Creakmentioning
confidence: 99%
“…Phrase-final creak refers to ends of phrases, especially utterances (Redi and Shattuck-Hufnagel 2001), that are produced with creaky voice or with creak so irregular that the "quasi-"periodic vibration assumed for voicing is called into question. Phrase-final creak is common across varieties of English, but is also attested in other languages, including Spanish (Garellek 2022;González et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Each DU could have up to three primary and secondary purposes, and the authors determined that two broad categories of sharing feelings and evaluations and of conveying information accounted for over 80% of the general communicative purposes. This approach is similar in some ways to Goffman's (1974) notion of frame, which delineates how an individual categorizes or makes sense of their social interactions. However, in my view, Biber et al (2021) offer a more clearly defined, empirically verified approach for determining the communicative purposes of discourse units within informal conversation.…”
Section: Organizing Conversational Interactionmentioning
confidence: 99%